Role of Hypoxia on Growth and Differentiation of Human Adipose Derived Stem Cells Grown on Silk Fibroin Scaffold Induced by Platelet Rich Plasma - Anggraini Barlian; Marselina Irasonia Tan; Ergha Widya Sarjana; Noviana Vanawati (Journal of Mathematical and Fundamental Sciences, 2021)
Previous research has proven that 10% platelet-rich plasma (PRP) can enhance growth and differentiation of human adipose derived stem cells (hADSC) grown on silk fibroin scaffold into chondrocytes. A low oxygen concentration (hypoxia) condition is an important factor that potentially affects the ability of hADSC to grow and differentiate. The objective of this research was to analyze the difference in growth and differentiation capacity of hADSC grown on salt leached silk fibroin scaffold supplemented by 10% PRP under normoxic and hypoxic conditions. The growth capacity of the hADSC was determined by MTT assay and differentiation was tested using glycosaminoglycan (GAG) content analysis, while chondrocyte markers were visualized with the immunocytochemistry (ICC) method. This research observed hADSC proliferation under normoxic and hypoxic conditions for 21 days. Visualization of type 2 collagen showed that it was more abundant under hypoxia compared to normoxia.  HIF-1α was only detected in the hADSC cultured in hypoxic conditions. In conclusion, culture under hypoxic conditions increases the capacity of hADSC to grow and differentiate into chondrocytes. This is the first study that has shown that hypoxia is able to enhance the proliferation and differentiation of hADSC grown on 3D salt leached silk fibroin scaffold supplemented by 10% PRP.